A Capoeira entre os fundamentos e movimentos de criação: um estudo sobre cultura, gênero e sexualidades - Caciatori, Eduarda Gava (2021)
This research followed and mapped two experiences of Contemporary Capoeira in the countryside of the state of São Paulo, seeking to identify the displacements in its current dynamics, highlighting their foundations and following the ongoing transformation and creation movements - taking questions relating to gender relations and sexualities, but also considering ethnic-racial and class markers. One of the spaces is the Centro de Referência LGBT de Campinas/SP, where Capoeira classes are held for the LGBTQIA + community, taught by Professor Luiz Otávio, Puma Camillê; the other space is the Capoeira academy “Cordão de Ouro Tatuí”, coordinated by Meriele, Professor Pepê, in the city of Tatuí/SP. Capoeira is a traditional popular manifestation that proposes to be bound to its essence and to preserve it, so, how do these processes of changes and resignifications occur? The aim of this research was to identify how this dialogue between preserving and creating in traditional popular culture happens, especially in these two specific Capoeira experiences. The research was based on the cartographic perspective and aimed to draw the route and record the ways in which these displacements are happening. It also sought to point out and discuss the relationship between Capoeira and popular education, highlighting the emancipatory potential of these practices.